Supplementary dataset to the article "Sustainability of Pasture Species Diversity in Forage Allowance-Based Stocking Methods in Subtropical Grasslands of Northeast Argentina" [Conjunto de datos] - Gandara, Luis; Ferrari Usandizaga, Silvana Consuelo; Pereira, Maria Mercedes; Riva De Neyra, Leonardo Atilio (Estación Experimental Agropecuaria Corrientes, INTA, 2025)
Hoja 1: Botanical composition: This dataset contains botanical composition records from subtropical grasslands in Northeast Argentina, evaluated under four pasture management treatments combining forage allowance and mowing practices. Each entry includes species name, family, dry matter percentage, and forage quality classification. The data spans multiple evaluation cycles and replicates, and is formatted for international use. -- Hoja 2: Non forage covered soil: Non forage covered soil: experimental data on the effect of mowing treatments under two grazing conditions (low and moderate forage allowance of 5 and 10 kg DM/ 100 kg LW/ day, respectively). Dates have been converted to the international format (YYYY-MM-DD) to facilitate integration into global data repositories. -- Study Location: INTA EEA El Sombrero, Corrientes, Argentina